The Intercultural Perspective in Paulo Freire’s Pedagogy of the Oppressed - Maviglia, Domenica (Studi sulla Formazione/Open Journal of Education, 2019)
This paper proposes an intercultural interpretation of the “Pedagogy of the Oppressed” by Paulo Freire highlighting how his pedagogical vision reflects a valid perspective of fusion between pedagogical theory and intercultural educational practice useful for reading, interpreting and addressing the crucial issues of contemporary educational debate and the most urgent social problems of our times.